Improving the Antitumor Activity of Squalenoyl‐Paclitaxel Conjugate Nanoassemblies by Manipulating the Linker between Paclitaxel and Squalene. Issue 1 (4th December 2012) - Caron, Joachim; Maksimenko, Andrei; Wack, Séverine; Lepeltier, Elise; Bourgaux, Claudie; Morvan, Estelle; Leblanc, Karine; Couvreur, Patrick; Desmaële, Didier
Abstract A series of new lipid prodrugs of paclitaxel, which can be formulated as nanoassemblies, are described. These prodrugs which are designed to overcome the limitations due to the systemic toxicity and low water solubility of paclitaxel consist of a squalene chain bound to the 2′‐OH of paclitaxel through a 1, 4‐cis, cis‐dienic linker. This design allows the squalene‐conjugates to self‐assemble as nanoparticular systems while preserving an efficient release of the free drug, thanks to the dienic spacer. The size, steric hindrance, and functional groups of the spacer have been modulated. All these prodrugs self‐assemble into nanosized aggregates in aqueous solution as characterized by dynamic light scattering and transmission electron microscopy and appear stable in water for several days as determined by particle size measurement. In vitro biological assessment shows that these squalenoyl–paclitaxel nanoparticles display notable cytotoxicity on several tumor cell lines including A549 lung cell line, colon cell line HT‐29, or KB 3.1 nasopharyngeal epidermoid cell line. The cis, cis‐squalenyl‐deca‐5, 8‐dienoate prodrug show improved activity over simple 2′‐squalenoyl‐paclitaxel prodrug highlighting the favourable effect of the dienic linker. The antitumor efficacy of the nanoassemblies constructed with the more active prodrugs has been investigated on human lung (A549) carcinoma xenograft model in mice. The prodrug bearing the cis, cis‐deca‐5, 8‐dienoyl linker shows comparable antitumor efficacy to the parent drug, but reveals a much lower subacute toxicity as seen in body weight loss. Thus, nanoparticles with the incorporated squalenoyl paclitaxel prodrug may prove useful for replacement of the toxic Cremophor EL.